(untitled) (Journal of Comparative Social Work, 2018)
The purpose of this study was to examine femicide cases in Iceland, which is a small Nordic welfare society. Cases of femicide were explored during a 30-year time period from 1986-2015. Femicide was defined as the murder of a woman by a partner, former partner or related to passion. Verdicts and news of the incidents were analysed. Verdicts were found using the search machine Fons Juries, run by a private legal company, which collected all verdicts from the Supreme Court from 1920, and all verdicts from the district courts existing in electric form. News that included murders of women was collected from websites of the main newspapers in Iceland. Eleven women were killed during this time period according to the definition used in this study. Most of the incidents happened in the home of the perpetrator, victim or both. Nearly all of them took place during the night or in the evening during weekends, with more incidents occurring during cold and dark months than brighter and warmer months. All of them took place in the capital city or in that area. Strangulation was the most common murder method, followed by stabbing the woman with a knife. Only one woman was shot, and that perpetrator was the only one who killed himself afterward. The mean age of the perpetrators was 29. Most of them had a low level of education or their education was unknown, and had a low paying job. Two-thirds of them were under the influence of alcohol and/or drugs when the incident happened and the majority had a psychiatric problem, mainly personality disorders or symptoms of such disorders, such as antisocial personality disorder. Even though it is rare, femicide incidents do exist in a small Nordic welfare society such as Iceland, despite an extensive welfare policy and gender equality.